Application of Interactive Hots e-Modules Based on Gamification in Improving Learning Outcomes in Islamic Religious Education Subjects for students at State Junior High School 1 Taluditi - Darmawati Darmawati; Muliani Muliani (Yayasan Adra Karima Hubbi, 2025)
Background. Critical thinking and creative design have not been optimally implemented and adopted in learning. HOTS e-modules for teacher programs will help them analyze and maximize their teaching outcomes. Purpose. The purpose of this study is to develop HOTS content in the e-module of Islamic Religious Education subjects at SMPN 1 Taluditi, increase creativity in developing teaching strategies and methods, improve critical thinking. Method.The method used was R&D with the DDDE (Decide, Design, Develop, and Evaluate) model, which was chosen because it aligns with the objectives of developing HOTS-based interactive e-modules and gamification. A small-scale trial of the HOTS e-module was conducted by teacher experts and lecturers, while a large-scale trial was conducted by 22 students. Results.The results of the study showed that the gamification-based interactive HOTS e-module developed using the DDD-E model met the validity criteria with an average score of 3.89, was considered practical with an average score of 3.67, and demonstrated effectiveness, with 87.8% of students achieving a minimum test score of 70. ConclusionThis interactive HOTS e-module, developed using the DDD-E model, is valid, practical, and effective. It equips teachers with innovative tools to enhance critical thinking and student engagement, and promote better learning outcomes through gamified educational experiences.